2019
DOI: 10.31557/apjcp.2019.20.10.2935
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Filial Therapy on Depressive Symptoms of Children with Cancer and Their Mother’s Depression, Anxiety, and Stress: A Randomized Controlled Trial

Abstract: Background: Childhood cancer is an overwhelming life event that can completely change the lives of the sufferers and their parents. Todays, advances of medical science have shifted the fetal nature of childhood cancer to chronic one exposing children and their family to behavioral and psychosocial problems. The aim of this study was to investigate the effect of filial therapy on children's depressive symptoms and their mother's stress, anxiety, and depression. Materials and Methods: In this randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…Four studies compared the experimental condition to individual psychotherapy. In three of these studies, the family intervention was significantly better than individual psychotherapy at reducing depressive symptoms (Dietz et al, 2015; Ebrahimi et al, 2019; Spirito et al, et al, 2015); in the remaining study, both conditions improved symptoms but no group differences were found (Tompson et al, 2017). Three studies compared the experimental condition to treatment as usual or enhanced treatment as usual; one of the studies found that the experimental group was significantly better than treatment as usual at reducing symptoms (Israel & Diamond, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies compared the experimental condition to individual psychotherapy. In three of these studies, the family intervention was significantly better than individual psychotherapy at reducing depressive symptoms (Dietz et al, 2015; Ebrahimi et al, 2019; Spirito et al, et al, 2015); in the remaining study, both conditions improved symptoms but no group differences were found (Tompson et al, 2017). Three studies compared the experimental condition to treatment as usual or enhanced treatment as usual; one of the studies found that the experimental group was significantly better than treatment as usual at reducing symptoms (Israel & Diamond, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Control conditions in the studies on family interventions for depression included individual therapy modalities ( n = 4; Dietz et al, 2015; Ebrahimi et al, 2019; Spirito et al, 2015; Tompson et al, 2017), parenting groups ( n = 2; Luby et al, 2012; Poole et al, 2018), enhanced treatment as usual or treatment as usual ( n = 3; Diamond et al, 2010; Israel & Diamond, 2013; Esposito‐Smythers et al, 2019), family‐enhanced non‐directive supportive therapy ( n = 1; Diamond et al, 2019), waitlist ( n = 1; Luby et al, 2018), and placebo ( n = 1; Fristad et a., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wilford et al (2020), the combination of TCM and peer support-based health promotion improved parent emotional distress, social support, and sleep disturbances and children’s physical activity, cognitive outcomes, and QoL. The filial therapy used in Ebrahimi et al (2019), was beneficial for depression, anxiety, and stress experienced by mothers, but also depressive symptoms experienced by children. In Shoshani et al (2016), fulfillment of the child’s greater wish reduced distress, depression, and anxiety symptoms and improved HRQoL and hope.…”
Section: Results Of Interventionsmentioning
confidence: 99%
“…The results of Ashori and Karimnezhad (2019) revealed that play therapy training with FT model had a significant effect on the behavioral problems of children and resilience of deaf mothers. Ebrahimi et al (2019) concluded that using FT could reduce the anxiety, depression, and stress in parent of children with cancer. The findings of Mirzaie et al (2019) revealed that FT could improve the attention and hyperactivity of children with attention deficit hyperactivity disorder.…”
Section: Review Of the Researchmentioning
confidence: 99%